Effects of the COVID-19 pandemic and its repercussions on child development: An integrative review (Research, Society and Development, 2021)
The pandemic may have affected the mental health and impacted the routine of children around the world. This study aims to understand how children are experiencing the impacts of the pandemic and its repercussions on child development. An integrative review of national and international literature was conducted. The research was conducted in the months of March and April 2020, in the Pepsic, Scielo, and Google Academic databases.  The final sample was composed of 12 studies, these were grouped into four thematic categories: (1) Technology and mental health involving children during the COVID-19 pandemic; (2) The importance of parents talking about the process of death and dying with their children; (3) Childhood violence in the context of COVID-19 and (4) Information to maintain children's mental health. It was verified exacerbated use of technologies, difficulties of caregivers in dialoguing with their children about the process of death, as well as an increase in behavioral problems, child violence in children. We conclude that there is a need for preventive interventions to expand the coping strategies of child caregivers in order to minimize the damage to the mental health of the children and the family group during or after the pandemic.